A review of solar absorption chillers and thermal storage by phase change materials - Abdelwanes, Abdelsalam; King, Peter; Wijayantha, Upul K. G.; Patchigolla, Kumar; Renaldi, Renaldi (Sage, 2026)
The emergence of advanced absorption chillers designed for the effective utilisation of low-grade thermal energy indicates a notable advancement in the discipline of cooling technology. These chillers, which range from small air-cooled systems to larger solar-gas-fired units, are specifically designed to address the escalating requisites for environmentally sustainable cooling alternatives. This paper presents a comprehensive review of solar absorption chillers and their integration with thermal energy storage systems, with a focus on the application of phase change materials (PCMs). It analyses the performance and configurations of single, double, and triple-effect chillers, along with the role of various solar thermal collectors in delivering the required input temperatures for cooling applications. Sensible, thermochemical, and latent heat storage methods are explored, emphasising cascade PCM systems for improved thermal efficiency and load flexibility. While the review highlights the significant potential of solar-powered absorption chillers in advancing sustainable cooling, particularly in hot climates such as those found in Africa, it also identifies key research gaps. These include the limited analysis of medium-temperature cooling demand (2–12°C), the need for integrated thermal storage systems using PCMs for multi-level cooling demands, and the lack of region-specific feasibility studies in diverse African conditions. Overall, the paper offers valuable insights into optimising solar absorption cooling technologies through effective storage integration and system design, supporting their broader adoption in energy efficient, low carbon applications.
Keywords: Solar absorption chiller; thermal solar collectors; solar cooling; refrigeration demand; space cooling; phase change materials; 40 Engineering; 4016 Materials Engineering; 7 Affordable and Clean Energy; 4017 Mechanical engineering